Valuing indigenous cattle breeds in Kenya: An empirical comparison of stated and revealed preference value estimates - Riccardo Scarpa; P. Kristjanson; Adam Drucker; M. Radeny; E. S. K. Ruto; J. E. O. Rege (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this study we compare revealed and stated-preference approaches to value live-stock traits of cattle in Kenya. The premise is that much can be learnt about non-market values of indigenous animal genetic resources (AnGRs) from the use of multi-attribute stated-preference methods, if these compare well with revealed-preference results. The objective is to investigate the performance of choice experiments (CEs) in Maasai cattle trading, by conducting an external test of preference consistency. This involves comparing value estimates for cattle attributes derived from CEs data with those obtained using a hedonic analysis of actual transactions by the same population of traders, in the same markets and over the same period. If CEs perform well, they can be used to investigate values of those genetically-determined livestock traits currently not prominent in pastoralists' populations, but desirable candidates for breeding or conservation programmes (e.g. disease resistance). It is argued that these methods are important in developing countries where livestock are kept for economic reasons and for cultural and risk management functions which are critical to livelihood strategies, but not valued by markets. The results indicate that CEs estimates pass the external test and appear to be adequately precise in estimating values for cattle traits that are relevant in market transactions for Maasai traders. They may be, therefore, a promising tool for valuing phenotypic traits expressed by indigenous AnGRs.
Keywords: 330; Biodiversity values; genetic resources; stated preference; choice experiments; livestock values; non-market values; shorthorn East African zebu; Rinderhaltung; Artenvielfalt; Bewertung; Kenia